Vulnerabilities that Allow to Make Botnets from IoT Devices - Lohunov, Dmitriy; Masalskaya, E.A.; Gubkina, V.V. (Видавництво НГУ, 2017)
Nowadays people want each of their devices to be smart and connected to the network. This idea is called Internet of Things (IoT). The list of modern devices that support IoT includes smartphones, watches, appliances, cameras, cars and much more. It allows user to control its house just with one smartphone.
Keywords: Vulnerabilities; Botnets from IoT Devices